The influence of globalization processes on strategic development of human capital of industrial enterprises of Ukraine - Rovenska, V. (Економічний вісник Донбасу, 2018)
It has been determined that one of the tools that allows rapid response to changes in the environment, the growth of competition in all spheres of activity is a balanced system of indicators. A characteristic feature of this system of indicators is that it uses not only financial indicators that reflect the efficiency of the business entity in the past, but also does not solve the problems that arise in real-time, as well as the strategic integers enterprises to all employees, but also non-financial indicators that reflect the achievement of strategic goals in various aspects of business and at all levels of management. It has been proved that in order to ensure the quality of human capital and to intensify investment in its development in Ukraine it is necessary to promote the stimulation of the process of innovative development in educational institutions, supplemented by its introduction of innovative technologies in the field of higher education; ensure training of personnel in accordance with modern requirements of employers on their mobility, the ability to generate new ideas and readiness to implement innovations within the framework of strategic objectives of the enterprise. Визначено, що одним із інструментів, який дозволяє оперативно реагувати на зміни зовнішнього середовища, зростання конкуренції в усіх сферах діяльності є збалансована система показників. Характерною особливістю цієї системи показників є те, що вона використовує в якості методів управління діяльністю підприємств не тільки фінансові показники, які віддзеркалюють ефективність роботи господарюючого суб’єкту в минулому, що не вирішують проблеми, які виникають в режимі «реального часу», не дозволяють довести стратегічні цілі підприємства до всіх робітників, але й нефінансові показники, які відображають досягнення стратегічних цілей у різних аспектах бізнесу та на всіх рівнях управління. Доведено, що для забезпечення якості людського капіталу та активізації інвестицій у його розвиток в Україні необхідно сприяти стимулюванню процесу інноваційного розвитку в навчальних закладах, доповнивши його впровадженням інноваційних технологій у галузі одержання вищої освіти; забезпечити підготовку кадрів відповідно до сучасних вимог роботодавців за їхньою мобільністю, можливості генерувати нові ідеї і готовність до реалізації інновацій в рамках стратегічних цілей підприємства. Определено, что одним из инструментов, который позволяет оперативно реагировать на изменения внешней среды, рост конкуренции во всех сферах деятельности является сбалансирована система показателей. Характерной особенностью этой системы показателей является то, что она использует в качестве методов управления деятельностью предприятий не только финансовые показатели, которые отображают эффективность работы хозяйствующего субъекта в прошлом, что не решает проблем, которые возникают в режиме «реального времени», не позволяют довести стратегические целые предприятия до всех работников, но и нефинансовые показатели, которые отображают достижение стратегических целей в разных аспектах бизнеса и на всех уровнях управления. Доказано, что для обеспечения качества человеческого капитала и активизации инвестиций в его развитие в Украине необходимо оказывать содействие стимулированию процесса инновационного развития в учебных заведениях, дополнив его внедрением инновационных технологий в области получения высшего образования; обеспечить подготовку кадров соответственно современным требованиям работодателей по их мобильности, возможности генерировать новые идеи и готовность к реализации инноваций в рамках стратегических целей предприятия.